Self-medication pattern among children attending a tertiary hospital in South India: a cross-sectional study - Naaraayan, Sridevi A; Rathinabalan, I.; Seetha, V. (International Journal of Contemporary Pediatrics, 2016)
Background:Administration of medications by care-givers to children without medical consultation is termed self-medication. Published literature on self-medication pattern in Indian children is scanty. Primary objective of the study was to study the prevalence of self-medication. Secondary objectives were to study its characteristics and the relation between demographic characteristics and self-medication. Methods: This descriptive study was performed in the outpatient department of Institute of child health and hospital for children. All children between 1 month and 12 years of age who attended the outpatient department during a particular time of the day on particular days of week were included in the study. After noting down the demographic characteristics, history of self-medication was elicited. For children who self-medicated, inciting illness, name of drug, source, reason and adverse events were noted down. Prevalence of self-medication was expressed as proportion with 95% confidence interval. Relation between demographic factors and self-medication was determined using chi-square test. Results:Prevalence of self-medication was 32% (95% confidence interval 28-35%). Common illnesses leading to self-medication were fever, cough and cold. Commonly used drugs were paracetamol, anticold medications and antibiotics. Most of them used previous prescription to procure the drugs and previous experience on efficacy was the most common reason cited. Older children were more commonly self-medicated than the younger (p = 0.001). Conclusions:Self-medication is encountered in 32% of children attending the outpatient department of the hospital and is more common in older children.